114 BILIARY STRICTURE AFTER LIVER TRANSPLANTATION. (1st January 2005) - Barriga, J. A.; Tombazzi, C. R.; Waters, B.; Godely, R.; Vera, S. R.; Riely, C. A.; Shokouh-Amiri, H.
Abstract : Introduction: Biliary stricture is a common complication in post liver transplant patients. It occurs in 9 to 15% of cases. We present the experience at the University of Tennessee Liver Transplant Center in the endoscopic diagnosis and management of biliary strictures after orthotopic liver transplant (OLT). Aims and Methods: The aim of this study was to describe the incidence of biliary strictures in those liver transplantation recipients who underwent endoscopic retrograde cholangiopancreatography (ERCP) due to the clinical and laboratory suspicion of biliary stricture. Our population included consecutive patients who had an OLT in the period of October 2001 and August 2004; we also included patients that were transplanted before October 2001 who developed signs of biliary stricture and were referred for ERCP during the previously mentioned period of time. All patients were followed for 3 months to 3 years. Results: During October 2001 and August 2004 there were 104 OLTs. Twenty-one patients underwent ERCP (6 patients had the liver transplant before October 2001, 3 were referred from another hospital). ERCP was successful in 19/21 patients (90.4%). There were two failed ERCPs, one due to a pyloric obstruction and the other due to unsuccessful cannulation. Biliary stricture was found in 13 patients (68.4%). In 9 patients the stricture was found at the site of anastomosis. There were post-ERCP complications in 3 occasions (9.3%), 2 episodes of cholangitis in the same patient and one mild pancreatitis, each one requiring less than 48 hours of hospitalization. No severe complications were seen. Treatment of the strictures consisted of balloon dilatation and placement of 1 to 3 stents. The number of procedures perfomed per patient was between 1 and 4 (average: 1.8). After endoscopic treatment 10/13 patients improved, 6 of them with complete resolution of the stricture and 4 are still on treatment with stent exchange. Two patients died for causes unrelated to the stricture. One patient underwent surgical revision of an anastomosis of the donor's common hepatic and recipient's cystic duct. Conclusion: In our study the most common site of biliary stricture in the post OLT patients was found to be at the anastomosis (69%). In this series, most post-transplantations were successfully corrected with endoscopic treatment.